PENGEMBANGAN MEDIA AUDIO VISUAL MELALUI APLIKASI CARTOON STORY MAKER UNTUK MENINGKATKAN KETERAMPILAN BERBICARA DI KELAS V SEKOLAH DASAR - Bella Aprillia Sandi; Yuyu Yuhana; Encep Andriana (STKIP Persada Khatulistiwa Sintang, 2023)
Most students are not confident in the learning process because students are less interested in speaking activities, when doing speaking exercises students look tense, this situation results in students not being used to speaking and the language used is still lacking, so the conversation is still stuttering the process of speaking skills applied by the teacher is still not attractive, thereby reducing the interest and enthusiasm of students. The purpose of this study was to determine the improvement of students' speaking skills in class V. The method used by this researcher was Research and Development (R&D) with procedures the research refers to the 4D model by Thiagarajan which consists of 4 stages, namely define, design, develop, and disseminate. The data collection is in the form of tests, observations, interviews, questionnaires, documentation, observation sheets, research instruments. The data analysis technique is validation questionnaire analysis and user response, pre-test, post-test, and indicators of success. The results of this study indicate that audio-visual media through the Cartoon Story Maker application is very feasible to improve the speaking skills of grade 5 students. This is evidenced by the validation results from two media experts with a percentage of 85.8% in the category